2014
DOI: 10.3892/or.2014.3420
|View full text |Cite
|
Sign up to set email alerts
|

C5a promotes the proliferation of human nasopharyngeal carcinoma cells through PCAF-mediated STAT3 acetylation

Abstract: The anaphylatoxin C5a is a chemoattractant that can induce various inflammatory responses in vivo via the C5a receptor (C5aR). There is emerging evidence that C5a is generated in the cancer microenvironment. However, the role of C5a in human nasopharyngeal carcinoma (NPC) remains largely unclear. Thus, the present study aimed to examine the direct influence of C5a stimulation on the proliferation of human NPC cells and to identify the underlying molecular mechanisms. The effects of C5a stimulation on the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…Similar to Elp3, PCAF has been shown to acetylate non-histones proteins such as β-catenin (Ge et al, 2009), Akt1 (Zhang et al, 2015), Stat3 (Cai et al, 2014) and lin28 (Wang et al, 2014). It would be interesting to test whether PCAF is also involved in the regulation of Cx43 acetylation in the developing cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Elp3, PCAF has been shown to acetylate non-histones proteins such as β-catenin (Ge et al, 2009), Akt1 (Zhang et al, 2015), Stat3 (Cai et al, 2014) and lin28 (Wang et al, 2014). It would be interesting to test whether PCAF is also involved in the regulation of Cx43 acetylation in the developing cortex.…”
Section: Discussionmentioning
confidence: 99%
“…NPC cells were transfected with pcDNA3.1/Akt1-His or pGCsi-U6/neo/GFP using Lipofectamine 2000 according to a previously described method (28). Cells were seeded into 6-well plates at a density of 1×10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…For certain studies, co-immunoprecipitation experiments were performed using an antibody against t-Akt1 according to a previously described method (28). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas gC1qR promoted angiogenesis and tumor growth, cC1qR stimulated the phagocytosis of tumor cells and was detrimental to tumor growth . Moreover, C1q was able to promote angiogenesis, as well as adhesion, proliferation, and metastasis of melanoma tumor cells independently of complement activation . The importance of other complement components in tumor biology was elegantly demonstrated by Bonavita et al., who reported that the pentraxin‐related protein PTX3 acts as an oncosuppressor regulating complement‐associated inflammation in cancer.…”
Section: Complement Activation In Cancermentioning
confidence: 99%